Storyworlds: the tiger and the jackal - Hamlyn, Gill; Terry, Michael Hamlyn, Paul (Heinemann UK, 1997)
In the Storyworlds tale "The Tiger and the Jackal," a cunning jackal tricks a powerful tiger into believing that he can help the tiger catch more prey. The jackal leads the tiger to a well, claiming that there are many deer inside. The tiger, eager to catch more prey, jumps into the well, but the jackal quickly runs away. The tiger is trapped in the well, unable to climb out.